Ethnic characteristics of physical and mental development of children, adolescents and youth in the Republic of Tuva (literature review) - Smirnova, Olga V.; Ovcharenko, Elizaveta S.; Kasparov, Eduard V. (The New Research of Tuva, 2026)
The article presents a review of scientific studies on the ethnic characteristics of the physical and mental development of children, adolescents and youth of the indigenous population of the Republic of Tuva over the past 25 years. The analysis revealed a number of general physiological features in the formation of physical development among representatives of the Tuvan ethnic group. Data on secular changes in the anthropometric characteristics of children and adolescents in the Republic of Tuva are considered. Studies are noted that describe ethnic features manifesting from birth, characterized by smaller longitudinal body dimensions, a predominance of disharmonious physical development due to excess body weight, and a markedly higher tension of adaptive mechanisms compared to Russian peers. At the same time, the Republic of Tuva shows a relatively favorable situation in terms of indicators of intellectual development of children, adolescents and youth compared to other regions of Russia, which is associated, among other factors, with large-scale measures to address iodine deficiency in this territory, against the background of a difficult situation with suicidal behavior among children and adolescents. The review highlights the insufficiency and fragmentary nature of scientific data on the physical and mental status of representatives of the Tuvan nationality, especially in younger age groups. The need is emphasized for a comprehensive approach to studying health indicators in children, adolescents and youth of the Republic of Tuva and for developing additional screening and preventive medical programs that take into account the ethnocultural characteristics of the region, as well as for adapting social support measures to improve the living conditions and quality of life of this small-numbered population of Russia.